2013
DOI: 10.1088/0004-637x/779/2/145
|View full text |Cite
|
Sign up to set email alerts
|

A Tidally Stripped Stellar Component of the Magellanic Bridge

Abstract: Deep photometry of the Small Magellanic Cloud (SMC) stellar periphery (R = 4 • , 4.2 kpc) is used to study its line-of-sight depth with red clump (RC) stars. The RC luminosity function is affected little by young ( 1 Gyr) blue-loop stars in these regions because their main-sequence counterparts are not observed in the color-magnitude diagrams. The SMCs eastern side is found to have a large line-of-sight depth (∼23 kpc) while the western side has a much shallower depth (∼10 kpc), consistent with previous photog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 53 publications
(80 reference statements)
5
111
1
Order By: Relevance
“…3. Common sources list: Early on in the development of PHOTRED, there were issues with constructing good PSFs for the deep (280 s), intermediate-band DDO51 observations for the MAPS survey (Nidever et al 2011(Nidever et al , 2013; which was the main motivation for writing PHOTRED). This was because there were a lot of point-like cosmic rays that overwhelmed the small number of real sources and made it difficult to create a good PSF source list just by culling via morphological parameters.…”
Section: Daophotmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Common sources list: Early on in the development of PHOTRED, there were issues with constructing good PSFs for the deep (280 s), intermediate-band DDO51 observations for the MAPS survey (Nidever et al 2011(Nidever et al , 2013; which was the main motivation for writing PHOTRED). This was because there were a lot of point-like cosmic rays that overwhelmed the small number of real sources and made it difficult to create a good PSF source list just by culling via morphological parameters.…”
Section: Daophotmentioning
confidence: 99%
“…The MAPS survey used photometrically selected red giant stars to find that the older SMC stellar population followed the same exponential profile from the center of the SMC out to ∼7°.5, but that beyond that there was a break in the radial profile with stars extending out to ∼11°(later confirmed with DES data by Pieres et al 2017), potentially representing a classical stellar halo of the SMC. In addition, Nidever et al (2013) found evidence for a stellar component of the tidally stripped Magellanic Bridge; more recently, Belokurov & Koposov (2016) used Gaia DR1 data to find both young and old stellar bridges, although they are not spatially coincident, between the Clouds. Finally, Pieres et al (2017) used DES data to discover a stellar overdensity in the northern region of the SMC (at ∼8°) that might be a tidally stripped dwarf galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…regions (Subramanian & Subramaniam 2009;Nidever et al 2013;Scowcroft et al 2016). The 0.1 mag deviations allowed in this work give LOS depths of ∼5.7 kpc and ∼4.6 kpc for the S/LMC.…”
Section: Ranges For Fitted Fundamental Parametersmentioning
confidence: 99%
“…The Small Magellanic Cloud (SMC), in particular, has an intriguing structure with a large extent along the line of sight (e.g. Subramanian & Subramaniam 2012;Nidever et al 2013;de Grijs & Bono 2015, and references therein) and a morphology that clearly depends on stellar population age (e.g. Cioni et al 2000a;Zaritsky et al 2000;Dobbie et al 2014;Subramanian & Subramaniam 2015;Deb et al 2015;Rubele et al 2015).…”
Section: Introductionmentioning
confidence: 99%